ANALISIS KEKERASAN DAN STRUKTUR MIKRO BAJA 304 DENGAN VARIASI HOLDING TIME - Tsamroh, Dewi 'Izzatus; Pungky Eka Setyawan; Andrian Dwi Kristianto (Universitas Islam Malang, 2023)
Metallurgy is the science that studies the properties of metals and their alloys through the analysis of their structures. Metal structure and alloys are the determining factors of the steel microarrangement that affect metal properties. The purpose of this study was to determine the strength and hardness of steel 304. This study used an experimental method by treating the workpiece and then characterizing it to see the results. In the hardness test it was concluded that a temperature does not affect the level of hardness of a specimen. While the cooling medium greatly affects the level of hardness. The higher the viscosity of a cooling fluid, the higher the hardness formed. Microstructural testing concluded that temperature and cooling media both have an effect on the formation of pearlite and ferrite in a material. If the temperature is the same and the fluids have the same properties, then the pearlite and ferrite contents will be the same. Pearlite will easily form at high temperatures with a high viscosity of the coolant, while ferrite will easily form if the temperature is low with a high fluid viscosity.